2021
DOI: 10.3765/plsa.v6i1.4970
|View full text |Cite
|
Sign up to set email alerts
|

“Problematic phonemes” and German /ɛ:/: An acoustic analysis

Abstract: The decision to include or exclude phonemes in the description of a language is not always straightforward; presentations of the phoneme inventory of Modern Standard German (MSG) often include a discussion of why /ɛ:/ is problematic as a phoneme. This study describes the acoustic realization of /ɛ:/ in comparison to /e:/ in spoken German, specifically South Westphalian. 39 native German speakers produced /ɛ:/ and /e:/ in hVt non-word frames and vowel productions were measured for: (1) first and second formants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In one study, only minor acoustic differences between the two vowels were found, which can be attributed to the fact that most speakers investigated in this study were from northern Germany ( Simpson, 1998 ). Most other acoustic analyses show differences in the pronunciation of the two vowels for speakers from different regions in Germany ( Sendlmeier and Seebode, 2006 ; Schoormann et al, 2019 ; Predeck et al, 2021 ). Results from the acoustic analysis of the corpus German Today ( Kleiner, 2011 , 2015 ) exhibit the tendency toward a merger in northern and eastern Germany as well as in Austria, while the south-west of Germany and Switzerland maintain a distinction (see Frank, in preparation ).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, only minor acoustic differences between the two vowels were found, which can be attributed to the fact that most speakers investigated in this study were from northern Germany ( Simpson, 1998 ). Most other acoustic analyses show differences in the pronunciation of the two vowels for speakers from different regions in Germany ( Sendlmeier and Seebode, 2006 ; Schoormann et al, 2019 ; Predeck et al, 2021 ). Results from the acoustic analysis of the corpus German Today ( Kleiner, 2011 , 2015 ) exhibit the tendency toward a merger in northern and eastern Germany as well as in Austria, while the south-west of Germany and Switzerland maintain a distinction (see Frank, in preparation ).…”
Section: Introductionmentioning
confidence: 99%